What influences where they seek care? Caregivers' preferences for under-five child healthcare services in urban slums of Malawi: A discrete choice experiment - Darker, Catherine; Lungu, Edgar Arnold; Obse, Amarech Guda; Biesma, Regien (My University, 2018)
Access to and utilisation of quality healthcare promotes positive child health outcomes. However, to be optimally utilised, the healthcare system needs to be responsive to the expectations of the population it serves. Health systems in many sub-Saharan African countries, including Malawi, have historically focused on promoting access to health services by the rural poor. However, in the context of increasing urbanisation and consequent proliferation of urban slums, promoting health of children under five years of age in these settings is a public health imperative. We conducted a discrete choice experiment to determine the relative importance of health facility factors in seeking healthcare for childhood illnesses in urban slums of Malawi. Caregivers of children under five years of age were presented with choice cards that depicted two hypothetical health facilities using six health facility attributes: availability of medicines and supplies, thoroughness of physical examination of the child, attitude of health workers, cost, distance, and waiting time. Caregivers were asked to indicate the health facility they would prefer to use. A mixed logit model was used to estimate the relative importance of and willingness to pay (WTP) for health facility attributes. Attributes with greatest influence on choice were: availability of medicines and supplies (β = 0.842, p<0.001) and thorough examination of the child (β = 0.479, p <0.001) with WTP of MK3698.32 ($11) (95% CI: $8–$13) and MK2049.13 ($6) (95% CI: $3–$9) respectively. Respondents were willing to pay 1.8 and 2.4 times more for medicine availability over thorough examination and positive attitude of health workers respectively. Therefore, strengthening health service delivery system through investment in sustained availability of essential medicines and supplies, sufficient and competent health workforce with positive attitude and clinical discipline to undertake thorough examination, and reductions in waiting times have the potential to improve child healthcare utilization in the urban slums.
PUBLISHED
Keywords: Malawi; Healthcare services; Children's health; Ageing; CHILD HEALTH; Health